Advantages of Laparascopic Method in Gynecology (Eurasian Medical Research Periodical, 2022)
This article discusses the advantages of laparoscopic method in gynecology, which is one of the endoscopic methods of modern medicine, methods of treatment and laparoscopic appendectomy.